Anna-Maria Meiser: capstone - Meiser, Anna-Maria, artist (Colorado State University. Libraries, 2020)
The artist's statement: I am an electronic artist who explores relationships and examines shared human experience. I enjoy observing the pull between opposing forces and creating bridges between subject matter through electronic art. I build digital expressions through sound, video, code, and stop motion works. As an artist I am often drawn to creating works that discuss unique aspects of my identity or human experience. My earliest work as a student often explored loss and the division between running out of time and time continuing without you. I tried to make sense of the loss of my parents through digital imagery and sound. I used props from my time in hospitals and arranging funerals to create stop motions that told my story in playdough and colorful antihistamine pills. As I continued my studies in electronic art, my interests broadened and I felt the influence of other electronic artists such as Yayoi Kusama, and Kristin Lucas impacting my art. At CSU I have explored many more relationships between topics such as micro and macro destruction, humanities survival versus the climate crisis, and most recently the relationships between humans and technology such as female identity within the digital age. Discovery, exploration, and connectivity unify my various bodies of work and have become a significant part of my process. As a student, I have spent most of my time researching other great artists and movements, focusing on experimentation, and pushing my work out of my comfort zone. As I grow in my skill and adopt new software’s such as Unreal Engine and P5.js I find my focus narrowing. I am currently feeling inspired to create works that express the volatile nature of our current pandemic. While my most recent works are videos pieces discussing it, I am also undertaking projects in which I am learning how to create art in three dimensional digital environments and VR. My goal is to incorporate these new skills into future artistic endeavors.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art